Hubungan Pola Asuh Orang Tua dengan Kejadian Gizi Kurang di Puskesmas XIII Koto Kampar II - Prasetya, Yeni Eka; Syahda, Syukrianti; ZR, Zurrahmi (Evidence Midwifery Journal, 2023)
Around 52 million (7.7%) children under 5 years globally experience malnutrition. The prevalence of malnutrition in Indonesia in 2019 was 17.6% and in 2020 there was an increase of 19.9%. The aim of this study was to determine the relationship between parenting style and the incidence of malnutrition in toddlers in the Work Area of ??UPT Puskesmas XIII Koto Kampar II in 2022. The research method was an analytic survey with a cross-sectional design. The population of this study were all mothers who had toddlers totaling 535 toddlers. There were 84 samples in this study and the sample was taken using the Simple Random Sampling technique. Data analysis using univariate and bivariate with chi square test. The statistical test results obtained a p value = 0.001 (? 0.05), which means that there is a relationship between parenting parents and the incidence of malnutrition in toddlers in the Work Area of ??UPT Puskesmas XIII Koto Kampar II in 2022. It is hoped that respondents will always actively participate in posyandu so that they can determine the development of nutritional status in infants